2014
DOI: 10.1016/j.rbmo.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aneuploidy, pregnancy and live birth rates between day 5 and day 6 blastocysts

Abstract: Comprehensive chromosome screening is typically used for aneuploidy analysis of blastocysts. It is believed that either day of blastocyst development is acceptable. Euploidy rates and outcomes were examined between day 5 and day 6 blastocysts in two studies. First, euploidy rates of day 5 and day 6 blastocysts were examined on a per-embryo and per-patient basis. Second, outcomes were compared when only euploid day 5 or day 6 blastocysts were transferred in a cryopreserved embryo transfer cycle. In cycles (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 27 publications
4
42
2
3
Order By: Relevance
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Although all studies have reported the pregnancy outcomes following transfer of frozen‐thawed blastocysts that had developed to blastocyst stage on day 5 or day 6, studies included in present meta‐analysis varied in terms of the number of embryo transferred and the chromosomal status of blastocysts. Only three studies transfer euploid blastocysts . Five studies only transfer one embryo per cycle, while remaining studies transfer no more than two blastocysts or more than two blastocysts per cycle .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhan et al reported a significant higher euploid rates in D5 blastocysts than in D6 blastocysts (51.6% vs. 34.0%) [27]. Taylor et al also found that euploid rates were significantly higher in D5 blastocysts than in D6 blastocysts (55.8% vs. 44.6%,P = 0.0014), and when only euploid D5 or D6 blastocysts were transferred during FET cycles, there were no significant differences between them regarding the CPR, IR, or ongoing/live birth rates [28]. Similarly, Capalbo et al found that the ongoing pregnancy rate of euploid D5 and D6 blastocysts was similar(48.8% and 51.2%, respectively) [29].…”
Section: Discussionmentioning
confidence: 96%